Peranan Budaya Organisasi, Kepemimpinan dan Strateji, untuk Meningkatkan Kinerja (Studi pada Industri Komponen Kendaraan Bermotor di Indonesia) - Andi Subroto; Eka Afnan Troena; Armanu Thoyib; Ubud Salim (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This research integrative built a research model in order to give comprehensive understanding how the contribution of organization culture, leadership and strategy to increase organization performance, how the variables related to each other and answer the gap in the previous research about organization culture and organization performance. The Study was conducted at Car Motor Component Industry in Indonesia using primary and secondary data. The research samples were 150 companies as member of GIAMM in all regions of Indonesia. The sampling technique used was Purposive Sampling Plan.The research result shows that the strong leadership and effective strategy have important role to increase organization performance. Organization culture does not appear directly influence the organization performance, but indirectly supports the strategy implementation to increase organization performance. Leadership has the strongest role in increasing organization performance, but it still has constraint in its role as strategic leadership, that is to build strong organization culture. Leadership and organization culture are proved to influence each other. Likewise, leadership and organization culture indirectly influence each other through a strategy to increase organization performance.Keywords: Organization Culture, Component Industry, Leadership, Organization Performance and Strategy.